A water extract of Malva verticillata seeds suppresses osteoclastogenesis and bone resorption stimulated by RANK ligand. Issue 1 (December 2016) - Shim, Ki-Shuk; Lee, Chung-Jo; Yim, Nam-Hui; Ha, Hyunil; Ma, Jin
Abstract Background Malva verticillata seeds are used as a therapeutic medicine to treat kidney dysfunction in traditional Chinese medicine (TCM). TCM has suggested that herbal medicine tonifying kidney function may have beneficial effect on bone metabolism. Methods Osteoclastogenesis was examined in bone marrow macrophages by measuring tartrate-resistant acid phosphatase (TRAP) activity and counting the number of TRAP-stained multinuclear cells. The activation of receptor activator of nuclear factor-kB (RANK) ligand signaling, and the expression of c-Fos and nuclear factor of activated T-cells, cytoplasmic 1 (NFATc1) were investigated by western blot analysis. Transcription factor and bone resorption marker mRNA levels were evaluated using real-time quantitative polymerase chain reaction. The bone resorption activity of mature osteoclast was examined in osteoclasts cultured on a hydroxyapatite-coated culture plate. Results A water extract ofM. verticillata seeds (WEMV) inhibited osteoclastogenesis stimulated by RANKL. WEMV also strongly inhibited expression of c-Fos and NFATc1 as well as phosphorylation of c-Jun N-terminal kinase, p38, I-kBα, and phospholipase γ2. Furthermore, WEMV significantly attenuated osteoclast resorption activity and downregulated mRNA expression of resorption markers. Conclusion These results demonstrate that WEMV inhibits osteoclastogenesis and bone resorption by suppressing the RANKL signaling pathway and suggest thatM. verticillata seeds may be used as a therapeutic candidate in complementary alternative medicine to treat pathological bone diseases.